Risk factors for unsuccessful tuberculosis treatment outcome (failure, default and death) in public health institutions, Eastern Ethiopia - Amante, Tariku Dingeta; Ahmed, Tekabe Abdosh (The Ethiopian Journal of Health Development, 2016)
Abstract Background: Unsuccessful TB treatment outcome is a serious public health problem. Therefore, this study aims at identifying risk factors for unsuccessful TB treatment outcome in eastern Ethiopia. Methods: Intuitional based case-referent study was employed on patientsâ€™ records in six TB clinics that had been providing DOTS in eastern Hararge Zone, Dire Dawa City Administration, and Harari Regional State. The cases were the records of TB patients registered as defaulter, dead and/or treatment failure. The controls were the patients who were cured or who completed the treatment. Multivariate logistic regression model was used to derive adjusted odds ratios (OR) at 95% CI to examine relationship between the unsuccessful TB treatment outcome and patients’ characteristics. Results: A total of 976 sample size (330 cases and 646 controls) were included. Of the cases 212 (64.2%) were dead, 100 (30.3%) defaulters and 18 (5.5%) were treatment failure. In this study, the factors independently associated with the unsuccessful TB treatment outcome include: lack of contact person(OR=1.37; 95% CI 1.14-2.9, P, .024), smear negative treatment category (OR=1.8; 95% CI 1.3-5.5,P, .028), smear positive sputum test at 2nd month after initiation of treatment ( OR=14; 95% CI 5.5-36, P,0.001) and HIV positive status( OR=2.5; 95% CI 1.34-5.7, P, 0.01 ). Conclusion: Many of the unsuccessful TB treatment outcomes wee because of death. TB patients who do not have contact person, smear negative treatment category, smear positive at second month after initiation of treatment and HIV positive status were significantly associated with unsuccessful treatment outcome. Targeted management of TB patients who are smear positive after second month of treatment initiation, HIV positive and do not have contact person should be considered through the entire TB treatment period. [Ethiop. J. Health Dev. 2014;28(1):17-21]